1980
DOI: 10.1095/biolreprod22.3.443
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Photoperiod on Reproductive Development in the Golden Hamster

Abstract: The effect of early lighting conditions on the sexual development of male and female golden hamsters was investigated, utilizing two experimental paradigms. In the first, hamsters were ex posed to one of several daily light cyc!es (14L:1OD, 6L:18D, 1L:23D, or constant darkness) from birth to 7 weeks of age. Weekly measurements of gonadal and sex accessory organ weights demon strated similar rates of reproductive development among treatment groups, indicating that the onset of puberty is not photoperiodically c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…In that study, although body weight was not affected by photoperiod, P. campbelli testes weight and uterine weight at 35 days were reduced under 8 h light:16 h darkness relative to 16 h light:8 h darkness (Ebling 1994). Therefore, the developmental pattern for reproductive tissues in P. campbelli is not the same as the 'develop and then regress' pattern described for golden hamsters (Darrow et al 1980). Thus, the developmental trajectories for reproduction in P. campbelli did not follow established patterns for P. sungorus or the golden hamster.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In that study, although body weight was not affected by photoperiod, P. campbelli testes weight and uterine weight at 35 days were reduced under 8 h light:16 h darkness relative to 16 h light:8 h darkness (Ebling 1994). Therefore, the developmental pattern for reproductive tissues in P. campbelli is not the same as the 'develop and then regress' pattern described for golden hamsters (Darrow et al 1980). Thus, the developmental trajectories for reproduction in P. campbelli did not follow established patterns for P. sungorus or the golden hamster.…”
Section: Discussionmentioning
confidence: 69%
“…This latter pattern is typical of the responses of juvenile golden hamster (M. auratus) to gestation in long days, and Photoperiod and hamster development rearing in short days (Gaston & Menaker 1967, Darrow et al 1980. The earlier study comparing these two species of Phodopus, however, also included measures of reproductive tissues at 35 days in addition to measures at 70 days (Ebling 1994).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous studies have demonstrated that FSH can induce follicular growth in the virtual absence of LH; however, estrogen production is severely impaired (McNatty et al 1979, Schoot et al 1992, Shemesh 2001. Given that serum LH levels are much lower in SD than in LD female hamsters (Darrow et al 1980, Dodge & Badura 2002, it is possible that FSH-dependent estrogen production by granulosa cells is substantially reduced due to a decrease in LH-induced androgen precursor production by theca cells. The observed lack of effect of rhFSH on uterine mass and vaginal patency, which are largely estrogen-dependent traits (Odum et al 1997, van Meeuwen et al 2007, Suzuki et al 2007, Baranda-Avila et al 2009), supports these conclusions.…”
Section: Long-term Rhfsh Supplementation In Sdsmentioning
confidence: 99%
“…The Syrian hamster (Mesocricetus auratus) undergoes a seasonal fluctuation in reproductive function following a photoperiodic-independent reproductive maturation (Darrow et al, 1980;Elliott and Goldman, 1981;Smith et al, 1982). Some species, unlike the Syrian hamster, are also dependent on the photoperiod for their reproductive maturation.…”
Section: Introductionmentioning
confidence: 99%